Characterization and Function of the Interaction of Angiogenin With Alpha-Actinin 2 - Weng, Chunhua; Dong, Haojie; Mao, Jiajia; Lang, Xiabing; Chen, Jianghua (Frontiers in Molecular Biosciences, 2022)
Angiogenin (ANG) is the first human tumor-derived angiogenic protein, which can promote angiogenesis and tumor growth. In the previous study, we identified alpha-actinin 2 (ACTN2), a cytoskeletal protein, as a direct interacting protein with angiogenin. However, the interaction between ANG and ACTN2 was not characterized in detail, which may provide information on the molecular mechanisms of ANG functions. In this study, we mapped the accurate binding domain and sites in ANG and ACTN2 respectively. In ANG, the residues from 83 to 105 are the smallest motif that can bind to ACTN2. We then use site mutation analysis to identify the precise binding sites of ANG in the interaction and found the 101st residue arginine (R101) represents the critical residue involved in the ANG-ACTN2 interaction. In ACTN2, the residues from 383 to 632, containing two spectrin domains in the middle of the rod structure of ACTN2, play important role in the interaction. Further, we validated the interaction of ACTN2-383–632 to ANG by GST-pull down assay. In functional analysis, overexpressed ACTN2-383–632 could impair tumor cell motility observably, including cell migration and invasion. Meanwhile, ACTN2-383–632 overexpression inhibited tumor cell proliferation and survival as well. These data suggest that an excess expression of ACTN2 segment ACTN2-383–632 can inhibit tumor cell motility and proliferation by interfering with the interaction between ANG and ACTN2, which provides a potential mechanism of ANG action in tumor growth and metastasis.